Nitro-Oleic Acid Induced Reactive Oxygen Species Formation and Plant Defense Signaling in Tomato Cell Suspensions - Arruebarrena Di Palma, Andrés (2018)
Nitrated fatty acids (NO2-FAs) are formed by the addition reaction of nitric oxide- and nitrite-derived nitrogen dioxide with unsaturated fatty acids. Nitrated fatty acids act as signaling molecules in mammals through the formation of covalent adducts with cellular thiols. The study of NO2-FAs in plant systems constitutes an interesting and emerging area. The presence of NO2-FA has been reported in olives, peas, rice and in Arabidopsis. To gain a better understanding of the role of NO2-FA on plant physiology, we analyzed the effects of exogenous application of nitro-oleic acid (NO2-OA) to tomato cell cultures. We found that NO2-OA induced reactive oxygen species (ROS) production in a dose-dependent manner via activation of NADPH oxidases, which requires calcium entry from the extracellular compartment and protein kinase activation, a mechanism that resembles the plant defense responses. NO2-OA-induced ROS production, expression of plant defense genes and led to cell death. The mechanism of action of NO2-OA involves a reduction in the glutathione cellular pool and covalently addition reactions with protein thiols and reduced glutathione. Altogether, these results indicate that NO2-OA triggers responses associated with plant defense, revealing its possible role as a signal molecule in biotic stress.